A Mobile Stroke Treatment Unit for Field Triage of Patients for Intraarterial Revascularization Therapy. Issue 6 (14th July 2015) - Cerejo, Russell; John, Seby; Buletko, Andrew B.; Taqui, Ather; Itrat, Ahmed; Organek, Natalie; Cho, Sung‐Min; Sheikhi, Lila; Uchino, Ken; Briggs, Farren; Reimer, Andrew P.; Winners, Stacey; et al.
ABSTRACT INTRODUCTION Favorable outcomes in intraarterial therapy (IAT) for acute ischemic stroke (AIS) are related to early vessel recanalization. The mobile stroke treatment unit (MSTU) is an on‐site, prehospital, treatment team, laboratory, and CT scanner that reduces time to treatment for intravenous thrombolysis and may also shorten time to IAT. METHODS Using our MSTU database, we identified patients that underwent IAT for AIS. We compared the key time metrics to historical controls, which included patients that underwent IAT at our institution six months prior to implementation of the MSTU. We further divided the controls into two groups: (1) transferred to our institution for IAT and (2) directly presented to our emergency room and underwent IAT. RESULTS After 164 days of service, the MSTU transported 155 patients of which 5 underwent IAT. We identified 5 historical controls that were transferred to our center for IAT. Substantial reduction in times including median door to initial CT (12 minute vs. 32 minute), CT to IAT (82 minute vs. 165 minute), and door to MSTU/primary stroke center departure (37 minute vs. 106 minute) were noted among the two groups. Compared to the 6 patients who presented to our institution directly, the MSTU process times were also shorter. CONCLUSION Our initial experience shows that MSTU may help in early triage and shorten the time to IAT for AIS.